REFLEKSI KEBENARAN: PRINSIP KEJUJURAN SEBAGAI KOMUNIKASI SPIRITUAL ANAK DI ERA DIGITAL - Muhamad Iqbal; Cesilia Prawening (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2018)
The digital era is shown by the swift flow of information that is directly consumed by every layer of society, including children. Children who always witness public lies with claims of religious truth result in low social and emotional attitudes of children. This type of research is library research and this research is a qualitative descriptive study. Research concludes that the principle of honesty through reflective efforts will provide space for awareness of God and humans. This paper contributes to describing the understanding of spiritual communication in the digital era